Anesthesia Preferences of Operating Room Staffs in Turkey - Arzu Esen Tekeli (Van Tip Dergisi, 2020)
INTRODUCTION: To determine which anesthesia method is preferred and why by the operating room staffs who are faced with anesthesia applications every day, when they need a surgery about themselves or their relatives. METHODS: A semi-structured questionnaire consisting of questions was sent to the 1000 operating room staffs who are working in different hospitals on different regions of Turkey by technological methods of communication (Google forms over the Internet, messenger, like WhatsApp). Age, gender, occupation and duration of occupation of participiants, whether or not anesthesia was applied to them, and if applied the method, which anesthesia method they would prefer or not and why, and which anesthesia method they suggest to their relations were asked in questionnaire. RESULTS: Of the participants aged between 20 and 60, 51.2% (n = 327) were men and 48.8% (n = 312) were women. 69 % (n = 440) of the participants indicated that anesthesia was applied to them for any reason, while 31% (n = 199) indicated that they were not anesthetized. While general anesthesia, regional anesthesia, peripheral nerve block methods were the most suitable methods for the participants,choice was regional anesthesia (spinal, epidural, combined spinal epidural anesthesia) with 47%. The answer to the question of which anesthesia method do you recommend to your relatives and patients has been predominantly regional anesthesia. DISCUSSION AND CONCLUSION: We found that regional anesthesia more preferred in the operating room staff in Turkey. We believe that it will be possible to find out the direction of anesthesia preferences through larger studies and this situation may be important in terms of labor and cost planning.